Frontispiece: Mesoscale Polarization by Geometric Frustration in Columnar Supramolecular Crystals. Issue 16 (4th April 2017) - Zehe, Christoph S.; Hill, Joshua A.; Funnell, Nicholas P.; Kreger, Klaus; van der Zwan, Kasper P.; Goodwin, Andrew L.; Schmidt, Hans‐Werner; Senker, Jürgen
Abstract : Organic Ferroelectrics In their Communication onpage 4432 ff., A. L. Goodwin, H.‐W. Schmidt, J. Senker, and co‐workers describe how supramolecular chemistry meets geometric frustration in the bulk structures of benzene‐1, 3, 5‐trisamides.